PENGARUH KEKUASAAN TERHADAP PERUBAHAN LAHAN HUTAN DI SURAKARTA TAHUN 1900-1998 - Primaditya, Krisnanda Theo; Saraswati, Iftikha (Keraton: Journal of History Education and Culture, 2022)
Changes in forest land is a phenomenon that accompanies human history. The role of the ruler is in the spotlight when forest land in an area is degraded. One of the areas that is experiencing a narrowing of forest land is Surakarta. From the colonial period to the New Order, Surakarta experienced a change in the face of the city, especially the loss of forests in the region. The purpose of this study is to reveal the influence of the rulers in Surakarta during the period 1900 to 1998 on forest loss in the Surakarta area. The historical method was used in the context of compiling this research because the temporal as the main discussion began in 1900 and ended in 1998. The researcher also focuses more on the environmental history approach so that this research can be used as criticism and suggestions for future policy makers. Developments designed by the authorities during the period 1900 to 1998 have sacrificed ecologically valuable assets, namely forests. The government's interest in the economic sector is believed to be the main factor in the loss of forest land in Surakarta. The city of Surakarta experienced modernization during the colonial period so that mobility in urban areas has increased. The government that has the power in development must open up new production areas to meet needs instead of economic interests. Even the autonomous rulers experienced changes in culture and traditions regarding forests because forest land was getting narrower. Forest degradation continued during the New Order era. The period of Suharto's rule made forest land in Surakarta increasingly invisible. The role of the first lady who is the son of the Surakarta area is the main factor at this time. Urban development has increased sharply with the provision of public facilities and infrastructure.